(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2026)
Listening is the most important skill for language learning because listening is the first basic skill and ability in learning a new language that must be learned by beginners acquire new words from what they listen to and develops faster than the other language skills which indicate that it makes simple the development of the other language skills⁠. The main problem in this research is that it is difficult for students to understand the material and slows down the learning process because they do not understand what the teacher explains. The objective of this research, the researcher use of media can be applied to increase students` interest in listening skills in an interesting way so that it is not boring, namely by using animation video. In this research, the researcher used quantitative approach to analyze the data. This research applied pre-experimental research design, involved pre-test, treatment, and post-test to measure students’ ability in listening skill. The total population of the research consisted of ninth grade students from MTsN 2 Kota Makassar during the 2023/2024 academic year. A sample of class lX.9 was obtained with a total of 31 students, consist of 12 boys and 19 girls. The result and findings showed that students have been successful in learning animation video and got the good result and test. The students of MTsN 2 Kota Makassar especially of class IX.9 have a big motivation in learning listening by using animation video and reality to improve students’ listening. The significance of the average score between pre-test and post-test were different. The result of pre-test was 70 and post-test was 87.4. It means that there was a significant difference between pre-test and post-test.